Blind Love - Collins, Wilkie, 1824-1889; Besant, Walter, 1836-1901 (Salt Lake City, UT : Project Gutenberg, 2005)
"Blind Love" by Wilkie Collins is an unfinished novel written in 1887-1889 and completed by Sir Walter Besant after Collins's death. Set against the backdrop of Irish political violence and the Fenian movement, the story follows Iris Henley, a bold Englishwoman who falls dangerously in love with Lord Harry Norland$1 (Ban Irishman involved in a squad of political assassins. Her devotion persists despite his criminal activities, embodying the "blind love" of the title as Collins links Irish independence struggles with questions of women's autonomy and choice. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Blind_Love_(novel)
Release date is 2005-04-01
Produced by James Rusk. HTML version by Al Haines.
Keywords: Domestic fiction; Married women -- Fiction; Conspiracies -- Fiction; Ireland -- Fiction; Suspense fiction; Secret societies -- Fiction